BOLA-DRB3 gene polymorphisms influence bovine leukaemia virus infection levels in Holstein and Holstein × Jersey crossbreed dairy cattle - Carignano, Hugo Adrian; Beribe, Maria Jose; Caffaro, María Eugenia; Amadio, Ariel; Nani, Juan Pablo; Gutierrez, Gerónimo; Alvarez, Irene; Trono, Karina Gabriela; Miretti, Marcos Mateo; Poli, Mario Andres (2017)
Bovine leukemia virus (BLV) infections, causing persistent lymphocytosis and lethal lymphosarcoma in cattle, have reached high endemicity on dairy farms. We observed extensive inter-individual variation in the level of infection (LI) by assessing differences in proviral load in peripheral blood. This phenotypic variation appears to be determined by host genetics variants, especially those located in the BoLA-DRB3 MHCII molecule. We performed an association study using sequencing-based typed BOLA-DRB3 alleles from over 800 Holstein and Holstein × Jersey cows considering LI in vivo and accounting for filial relationships. The DBR3*0902 allele was associated with a low level of infection (LLI) (<1% of circulating infected B-cells), whereas the DRB3*1001 and DRB3*1201 alleles were related to a high level of infection (HLI). We found evidence that 13 polymorphic positions located in the pockets of the peptide-binding cleft of the BOLA-DRB3 alleles were associated with LI. DRB3*0902 had unique haplotypes for each of the pockets: Ser13-Glu70-Arg71-Glu74 (pocket 4), Ser11-Ser30 (pocket 6), Glu28-Trp61-Arg71 (pocket 7) and Asn37-Asp57 (pocket 9), and all of them were significantly associated with LLI. Conversely, Lys13-Arg70-Ala71-Ala74 and Ser13-Arg70-Ala71-Ala74, corresponding to the DRB3*1001 and *1201 alleles respectively, were associated with HLI. We showed that the specific amino acid pattern in the DRB3*0902 peptide-binding cleft may be related to the set point of a very low proviral load level in adult cows. Moreover, we identified two BOLA-DRB3 alleles associated with a HLI, which is compatible with a highly contagious profile.